2014
DOI: 10.1002/anie.201308067
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Synthesis of Hydrogen Peroxide Using Platinum‐Promoted Gold–Palladium Catalysts

Abstract: The direct synthesis of hydrogen peroxide offers a potentially green route to the production of this important commodity chemical. Early studies showed that Pd is a suitable catalyst, but recent work indicated that the addition of Au enhances the activity and selectivity significantly. The addition of a third metal using impregnation as a facile preparation method was thus investigated. The addition of a small amount of Pt to a CeO2-supported AuPd (weight ratio of 1:1) catalyst significantly enhanced the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 20 publications
10
66
1
Order By: Relevance
“…Thus, it should be noted that the reason of the high oxidation activity of the Au/Pt/TiO 2 catalyst, especially of the 1Au/1Pt/TiO 2 sample, also could be due to hydrogen peroxide formation. Recently, Hutchings et al [80] reported the enhanced activity of Pt-doped bimetallic Au-Pd/CeO 2 catalyst in H 2 O 2 formation. Moreover, H 2 O 2 could be activated on the TiO 2 support as surface-stabilized peroxo-or/and hydroperoxo species (Ti-O 2 − or/and Ti-OOH), as it was proved by Bonino et al [81], or just decomposed to O-centered radicals leading to non-selective secondary hydroxyl group oxidation in 1,2-PD, and C C bond scission under the more severe conditions.…”
Section: Proposed Scheme Of 12-propanediol Oxidationmentioning
confidence: 98%
“…Thus, it should be noted that the reason of the high oxidation activity of the Au/Pt/TiO 2 catalyst, especially of the 1Au/1Pt/TiO 2 sample, also could be due to hydrogen peroxide formation. Recently, Hutchings et al [80] reported the enhanced activity of Pt-doped bimetallic Au-Pd/CeO 2 catalyst in H 2 O 2 formation. Moreover, H 2 O 2 could be activated on the TiO 2 support as surface-stabilized peroxo-or/and hydroperoxo species (Ti-O 2 − or/and Ti-OOH), as it was proved by Bonino et al [81], or just decomposed to O-centered radicals leading to non-selective secondary hydroxyl group oxidation in 1,2-PD, and C C bond scission under the more severe conditions.…”
Section: Proposed Scheme Of 12-propanediol Oxidationmentioning
confidence: 98%
“…[2][3][4][5] Meanwhile, recent years have witnessed a growing interest in palladium (Pd)-based nanomaterials due to their fascinating properties and potential applications in catalysts. [ 1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] Given that the reactivity and selectivity of a catalyst are highly dependent on specifi c pathways of reactions, it is imperative to decode the mechanism behind each reaction in an effort to achieve rational catalyst design. In particular, oxida-…”
Section: Introductionmentioning
confidence: 99%
“…Strong synergy between Au and Pd is also observed in catalysts for the direct synthesis of hydrogen peroxide [14] and the oxidation of toluene [15]. Recently, we have explored the addition of a third metal and we have shown that for AuPdPt catalysts the activity can be enhanced for both hydrogen peroxide synthesis [30] and alcohol oxidation [18]. With benzyl alcohol oxidation, the addition of platinum switches-off the formation of toluene.…”
Section: Au Catalysts and Improving Catalysyt Activitymentioning
confidence: 97%